FENOMENA KEKERASAN TERHADAP PEREMPUAN DI DALAM RUMAH TANGGA (Pandangan Mubalig) - Fatmariza, Fatmariza (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2012)
This study aimed to describe the views of the Mubalig of the phenomenon of violence against women in the household (KDRT). Violence against women in the household is often justified because society is understood as being legitimized in the understanding of religion as they learn from the preachers. Bias in understanding, interpreting, and conveying religious teachings to the people—especially with regards to the issue of violence against women in the household—causes the growing injustices against women. Conversely, if there is no bias in understanding, interpreting, and conveying religious teachings by preachers, it will be possible to minimize violence against women in the household.Key words: violence against women, Mubalig, biased religious teachings